Research on the Impact of Driverless Car Technology Development on Future Urban Rail Transit - GE Shiping (Chengshi guidao jiaotong yanjiu)
［Objective］ The possible impact of the development of driverless car technology on future urban rail transit is explored, and the role of driverless cars in urban transportation systems as well as their impact on the existing urban transportation structure are analyzed. ［Method］ The traffic characteristics of driverless cars are outlined, the impact of driverless cars on urban transportation structure is analyzed, and the specific impact of driverless cars on urban rail transit is discussed in detail. ［Result & Conclusion］ Driverless cars can improve traffic efficiency and passenger experience, which may lead to a decrease in short-distance passenger flow in urban rail transit, but long-distance passenger flow still is still highly dependent on it. The popularization of driverless cars will prompt urban rail transit planning to pay more attention to speed and efficiency, optimization of transportation connection between the central city and satellite cities, and promotion of the interoperability and information interaction of various transportation modes’information systems, thereby enhancing the intensity of urban transportation integration. The development of driverless cars will trigger major changes in urban transportation, requiring urban planners and transportation managers to take corresponding measures to adapt to technological development.